en - Fitriani, Nining (e-Journal of Linguistics; Vol 15 No 1 (2021): ejl-January, 2020)
The purpose of this study was to determine the perception of students majoring in accounting, batch 2019, STEKOM University Semarang on reading examination using google form. The method used in this research was descriptive quantitative. The location of the research was conducted in the Accounting Department of STEKOM University. The study population was 80 students majoring in accounting, batch 2019, STEKOM University, all of which were used as research samples. Sources of data in this study were primary and secondary data sources. Data collection techniques using a questionnaire or questionnaire and documentation study. Data analysis was carried out descriptively using SPSS 16. The results of this study stated that most students had the perception that the reading examination using google form was not good, and only a few students had the perception that the reading examination using google form was good. This is because the reading examination using google form has not been able to improve student scores. In addition, reading examination using google form is considered difficult and ineffective and inefficient.